Visceral Obesity Predicts Significant Fibrosis in Patients With Nonalcoholic Fatty Liver Disease. Issue 48 (December 2015) - Yu, Su Jong; Kim, Won; Kim, Donghee; Yoon, Jung-Hwan; Lee, Kyoungbun; Kim, Jung Ho; Cho, Eun Ju; Lee, Jeong-Hoon; Kim, Hwi Young; Kim, Yoon Jun; Kim, Chung Yong
Abstract : Abstract: Nonalcoholic fatty liver disease (NAFLD) is associated with visceral obesity. However, the association between visceral adipose tissue (VAT) area and fibrosis in NAFLD patients has not been completely established. This study was aimed to determine the relationship between the computed tomography-measured VAT area and significant fibrosis in NAFLD patients. A total of 324 NAFLD patients and 132 controls were evaluated by liver biopsy. NAFLD was diagnosed based on histological examinations and alcohol consumption <20 g/day. The NAFLD patients showed a higher age and gender-adjusted VAT area than the control group (86.1 ± 2.3 vs 56.7 ± 3.7, P < 0.001). The VAT area increased across the control, NAFLD without significant fibrosis, and NAFLD with significant fibrosis groups (54.9 ± 3.5, 80.6 ± 2.4, and 123.4 ± 6.4, P < 0.001). This association persisted after adjusting for multiple confounders ( P for trend = 0.028). A multivariate regression analysis demonstrated the VAT area was independently associated with NAFLD with significant fibrosis (F2–F4) (odds ratio [OR] 1.21 95% confidence interval [CI] 1.07–1.37 per 10 cm 2 increase of VAT area; OR 2.62 [per 1 – standard deviation (SD)] 95% CI 1.41–4.86). Moreover, a multivariate logistic regression analysis revealed the VAT area was independently associated with nonalcoholic steatohepatitis (NASH) in NAFLD (OR 1.17 95% CI 1.05–1.32 per 10 cm 2 increase of VAT area; OR 2.21 [per 1 – SD] 95% CI 1.25–3.89). Increased VAT area is independently associated with NASH or significant fibrosis and VAT might be a central target for lifestyle modifications in NAFLD patients.